Al-Intifa' bi al-Mustahdathat al-Taknulujiyah fi Ta'līm al-Lughah al-Arabiyah. - Mohammad Ahsanuddin (ALSINATUNA, 2016)
The rapid advancement of information and technology nowadays has brought about tremendous change in education. Computer and internet technology are commonly used in the teaching and learning process, such as the use of Computer Assisted Learning, Internet Based Learning and e-learning. This paper addresses the uses of technology in Arabic Language teaching and learning which covers the definition of technology, the characteristics of advanced technology, the benefit of technological advancement and how technology is used in Arabic Language Teaching.